Pre-transplant CD69+ extracellular vesicles are negatively correlated with active ATLG serum levels and associate with the onset of GVHD in allogeneic HSCT patients - Storci, Gianluca; Barbato, Francesco; Ricci, Francesca; Tazzari, Pier Luigi; De Matteis, Serena; Tomassini, Enrica; Dicataldo, Michele; Laprovitera, Noemi; Arpinati, Mario; Ursi, Margherita; Maffini, Enrico; Campanini, Elena; et al. (Frontiers in Immunology, 2023)
Graft Versus Host Disease (GVHD) is a major complication of allogeneic hematopoietic stem cell transplantation (HSCT). Rabbit anti-T lymphocyte globulin (ATLG) in addition to Calcineurin inhibitors and antimetabolites is a suitable strategy to prevent GVHD in several transplant settings. Randomized studies already demonstrated its efficacy in terms of GVHD prevention, although the effect on relapse remains the major concern for a wider use. Tailoring of ATLG dose on host characteristics is expected to minimize its side effects (immunological reconstitution, relapse and infections). Here, day-6 to day+15 pharmacokinetics of active ATLG serum level was first assayed in an explorative cohort of 23 patients, by testing the ability of the polyclonal serum to bind antigens on human leukocytes. Significantly lower levels of serum active ATLG were found in the patients who developed GVHD (ATLG_AUCCD45: 241.52 + 152.16 vs 766.63 +/- 283.52 (ug*day)/ml, p=1.46e-5). Consistent results were obtained when the ATLG binding capacity was assessed on CD3+ and CD3+/CD4+ T lymphocytes (ATLG_AUCCD3: 335.83+208.15vs903.54+378.78 (ug*day)/ml, p=1.92e-4; ATLG_AUCCD4: 317.75+170.70 vs 910.54+353.35 (ug*day)/ml, p=3.78e-5. Concomitantly, at pre-infusion time points, increased concentrations of CD69+ extracellular vesicles (EVs) were found in patients who developed GVHD (mean fold 9.01 + 1.33; p=2.12e-5). Consistent results were obtained in a validation cohort of 12 additional ATLG-treated HSCT patients. Serum CD69+EVs were mainly represented in the nano (i.e. 100nm in diameter) EVs compartment, expressed the leukocyte marker CD45, the EVs markers CD9 and CD63, and CD103, a marker of tissue-resident memory T cells. These latter are expected to set up a host pro-inflammatory cell compartment that can survive in the recipient for years after conditioning regimen and contributes to GVHD pathogenesis. In summary, high levels of CD69+EVs are significantly correlated with increased risk of GVHD, and they may be proposed as a tool to tailor ATLG dose for personalized GVHD prevention.